Clarification of Some Provisions of the Methodology for Matching Objects to Specific Firearms - A. S. Likhachev; M. A. Sonis (Теория и практика судебной экспертизы)
The paper clarifies some of the provisions of the «Methodology for matching objects to specific firearms» that lend themselves to varying interpretations or lack explicit requirements regarding examination conditions. A newly proposed algorithm is easy to apply in forensic practice and can be recommended as a supplement to the methodology in question.